Strategi Guru PAI dalam Menumbuhkan Kesadaran Ekoteologi di Kawasan Dataran Tinggi Gayo - Harkarisma Harkarisma; Ansor Ansor; Birrul Walidaini (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in fostering ecotheological awareness among students at SMP Negeri 15 Takengon. The study was conducted in Central Aceh Regency, a region characterized by its rich natural environment, strong Islamic traditions, and the distinctive local wisdom of the Gayo community, which emphasizes harmony between humans and nature. This research uses a qualitative approach with a field research design. Data were collected through in-depth interviews, observation, and documentation involving two PAI teachers, the principal, students, and environmental staff. Data analysis employed the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results show that PAI teachers apply strategies such as value-based learning, role modeling, habituation, religious activities, and environmental care practices integrated into daily school life. Students’ ecotheological awareness is reflected in their attitudes toward cleanliness, environmental responsibility, and their understanding that environmental stewardship is part of their religious obligation, although it is not yet fully optimal. Several challenges were identified, including low student awareness, lack of consistency in habits, and limited support for environmental programs. It can be concluded that PAI teachers play an important role in fostering ecotheological awareness through integrated and continuous strategies. Strengthening ecotheological values in Islamic education is essential to develop environmentally responsible students based on religious principles and local cultural values.